2021
DOI: 10.3389/fmicb.2021.790256
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Parasitic Pathogens as Risk Factors for Cancers in the Gastrointestinal Tract: A Review of Current Epidemiological Knowledge

Abstract: The oncogenic potential of viral infections is well established and documented for many years already. However, the contribution of (commensal) bacteria and parasites to the development and progression of cancers has only recently gained momentum, resulting in a rapid growth of publications on the topic. Indeed, various bacteria and parasites have been suggested to play a role in the development of gastrointestinal cancer in particular. Therefore, an overview of the current epidemiological knowledge on the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 217 publications
(462 reference statements)
0
9
0
Order By: Relevance
“…Vitamins, such as vitamin B9, thiamine, vitamin B2, niacin, vitamin K, vitamin B1, riboflavin, etc., are produced by bacteria, such as Bifidobacterium bifidum , Bacillus Subtilis , Escherichia coli , Bacteroidetes, and are involved in immunological function, cellular metabolism, cell proliferation and offer vitamin sources for hosts. Polyphenols produced by Clostridium , E. coli , Salmonella , and Bacteroides function as antioxidants, and reduce the risk of colon cancer and inflammation [ 38 , 46 , 47 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Vitamins, such as vitamin B9, thiamine, vitamin B2, niacin, vitamin K, vitamin B1, riboflavin, etc., are produced by bacteria, such as Bifidobacterium bifidum , Bacillus Subtilis , Escherichia coli , Bacteroidetes, and are involved in immunological function, cellular metabolism, cell proliferation and offer vitamin sources for hosts. Polyphenols produced by Clostridium , E. coli , Salmonella , and Bacteroides function as antioxidants, and reduce the risk of colon cancer and inflammation [ 38 , 46 , 47 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Pancreatic cancer has also been associated in several studies with oral microbiota composition (32)(33)(34). The presence of microbiota in the pancreas itself and their effect on carcinogenesis is a timely research topic, as similar findings have been discovered in multiple gastrointestinal cancers (35). However, as bile passes through the pancreas, potential biomarkers for pancreatic cancer, including metabolic products of bacteria, may be more prevalent in bile than in other bodily fluids (36).…”
Section: Discussionmentioning
confidence: 90%
“…Subsequently these data suggested that, S. stercoralis, is a cofactor for the growth of HTLV-1-induced lymphocytic carcinoma [94] . The link between S. stercoralis and HTLV-1 was supported by data showing that the prevalence of S. stercoralis above two-folds, increased in HTLV-1 patients as compared to HTLV-1 free individuals [95] . Moreover, infection with S. stercoralis can last a lifetime, and patients may be prone to chronic inflammation of the bowel and colon.…”
Section: Nematodesmentioning
confidence: 87%